GAGASAN PENGUJIAN KETETAPAN MAJELIS PERMUSYAWARATAN RAKYAT DALAM SISTEM PENGUJIAN PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Rudi Heriyanto Sihombing; Dodi Haryono; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Determination of Tap MPR/S notch below the Constitution in 1945 NRI order regulations bring consequences that TAP MPR/S must be aligned with the NRI Constitution 1945. In a sense the TAP MPR/S must not be contrary to the provisions of the Constitution of the NRI, 1945. In contrary to the Constitution of 1945, NRI then TAP MPR/S will lose their validity. In the event of a charge TAP MPR material/S contrary to Constitution 1945 NRI, surely TAP MPR/S that can be tested against the UUD 1945 NRI (test of constitutionality). Otherwise TAP MPR/S became the source of law and the basis for the formation of legislation that exists underneath.From the results of the research there were two basic problems that can be inferred. First, TAP MPR became a part of the type of order and the legislation with the position is above the law and under the Constitution in accordance with the principle of perjenjangannya legal norms. TAP MPR is the country's basic rules/rules of principal State and be the source for the formation of legal norms that are pinned to the laws and regulations that are below. The legal position of the MPR's statutes, adjust by law number. Second, the institutions of the State which are entitled to perform testing against TAP MPR is regeling based on TAP MPR Number I/MPR/2003 and the enactment of Act No. 12 of 2010 is MK. Author, Advice, we suggest you First, defining the MPR are arranged in a special Article in the ACT on the establishment of regulations governing its legal status and mechanism testing and hindsight. Second, be a material input to the ASSEMBLY in the framework of an amendment to the Constitution, the MPR Ordinance testing add into the authority of the COURT to conduct the test of constitutionality.Key Words: The Idea Of Testing-TAP MPR – Regulations